Предмет: Алгебра,
автор: Typayy
ПОООООООММММОООООГГГГИИИИТЕ ПЖПЖПЖПДДП
Приложения:
![](https://files.topotvet.com/i/1f9/1f90cc89fd6e126277ec439be6005721.jpg)
Ответы
Автор ответа:
0
Упростим выражение в скобках:
1. 1/(b²-2b+1)=1/(b-1)²
2. 1/(b²-1)=1/((b-1)(b+1)).
3. 1/(b-1)²+1/((b+1)(b-1))=(b+1+b-1)/((b+1)(b-1)²))=2b/((b+1)(b-1)²). ⇒
4. (b-1)²*2b/((b+1)(b-1)²)=2b/(b+1).
5. 2b/(b+1)+2/(b+1)=(2b+2)/(b+1)=2*(b+1)/(b+1)=2.
Похожие вопросы
Предмет: Физика,
автор: Amogus9877d
Предмет: Физкультура и спорт,
автор: khorova0107
Предмет: Окружающий мир,
автор: Fokjust
Предмет: Алгебра,
автор: Арен15
Предмет: Алгебра,
автор: valeriyamartinson